Study of histopathology of endometrium in perimenopausal women with abnormal uterine bleeding - Mishra, Jyoti; Nigam, Neha; Rathod, Ishwar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The objective was to evaluate the incidence and prevalence of different histopathological endometrial pattern in patients of abnormal uterine bleeding (AUB) in peri-menopausal women and analyse the type of various menstrual irregularities in AUB cases. Methods: In this study, 164 perimenopausal women aged 41-48 years have been taken having considered appropriate within the inclusion criteria. Histopathological examination was done after obtaining the endometrial curetting’s by Dilatation and curettage or office Pipelle’s canula. Results: Mean age group of subjects was found to be 44.05 years. Majority of subjects were of normal body mass index. Heavy menstrual bleeding was the chief complaint in majority of subjects. Ultrasound finding was leiomyoma in more than 73% subjects. Proliferative pattern of endometrium remained the finding in most of the individuals. Among AUB-M, hyperplasia without atypia occurred in 53.84% and hyperplasia with atypia occurred in 38.46% individuals. Conclusions: Leiomyoma was the most common etiology contributing towards AUB in the perimenopausal age group. The difference between adenomyosis and leiomyoma may not be easily made clinically as signs and symptoms of adenomyosis and leiomyoma are very similar. Thus, it is important to use histopathological examination as a complementary diagnostic tool in classifying the structural causes of AUB.